Mazus Enterprise : Lemang Griller / Muhamad Aiman Mohd Radzuan ...[et al.] - Mohd Radzuan, Muhamad Aiman; Azdha Shafawi, Muhammad Azim; Megat Azlan, Mohamad Zahirul Haziq; Zaidi, Muhammad Ikmal Hakim; Ghazali, Mohamad Helmi; Huharjay, Ikhwan Afiq (2016)
After several research, we have found that making lemang is not easy as we thought. It tocks really long time to make sure it cook completely. Basically, using traditional method may took 6 to 8 hours with fully monitored. Higher skill is needed in production of lemang. The lemang need to be rotated manually every 30 minutes. Other than that, using hollow bamboo stick may cause lots of problem. These problems appear to be major problem in production of lemang. Lemang griller is the best solution of these problems. Firstly, we provide a look alike hollow bamboo stick made of aluminum. So, it can be use many times without wasting bamboos. Then, human power can be minimized by using motor to rotates the aluminum stick. Basically, everyone can use this machine without any problem. It is a portable machine and may be use indoor and outdoor.